2001
DOI: 10.1001/archpsyc.58.10.909
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Performance in Long-term Cannabis Users

Abstract: Some cognitive deficits appear detectable at least 7 days after heavy cannabis use but appear reversible and related to recent cannabis exposure rather than irreversible and related to cumulative lifetime use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

39
458
3
20

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 589 publications
(520 citation statements)
references
References 36 publications
39
458
3
20
Order By: Relevance
“…This could relate to residual drug effects or withdrawal symptoms during early abstinence, less need for neural compensation, or a change in neurocognitive strategy as the brain adapts to different stages of sobriety. We did not observe a correlation between brain response and recency of marijuana use in this sample, but most neuropsychological recovery appears to occur during the first week of abstinence (Pope et al, 2001). Thus, there may be little change in neurocognitive functioning after 28 days of abstinence, or such an effect may be too subtle to detect with a relatively small sample.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…This could relate to residual drug effects or withdrawal symptoms during early abstinence, less need for neural compensation, or a change in neurocognitive strategy as the brain adapts to different stages of sobriety. We did not observe a correlation between brain response and recency of marijuana use in this sample, but most neuropsychological recovery appears to occur during the first week of abstinence (Pope et al, 2001). Thus, there may be little change in neurocognitive functioning after 28 days of abstinence, or such an effect may be too subtle to detect with a relatively small sample.…”
Section: Discussioncontrasting
confidence: 57%
“…However, it is unclear whether these neurocognitive findings only represent effects of recent use. Pope et al (2001) demonstrated deficits on verbal learning up to 7 days after use among current heavy marijuana users compared with former users and non-using controls. However, after 28 days of abstinence, current users performed similarly to former users and controls on all tests, suggesting that neurocognitive decrements may resolve within a month of abstinence (Pope et al, 2001).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This last issue regarding whether EBC performance is recoverable will be important to elucidate from a public health perspective. Current neuropsychological data suggest a recovery of cannabis-induced cognitive impairments after 1 month of abstinence (Pope et al, 2001;Harrison et al, 2002). However, these neuropsychological tasks are typically sensitive to distributed cortical networks not specific to cerebellar processes, as is the EBC procedure.…”
Section: Discussionmentioning
confidence: 99%